FENOMENA GAMOPHOBIA PADA GEN Z DAMPAK DARI KASUS PERCERAIAN ORANG TUA - Alifa Izzatun NIsa; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
The phenomenon of Gamophobia or the fear of establishing a marriage relationship among young people is increasing day by day along with the marriage rate in Indonesia which is decreasing day by day. if this phenomenon continues without any settlement efforts it can affect demographic construction in Indonesia. The purpose of this study was conducted to determine how the influence of parental divorce cases can have an impact on the phenomenon of Gamophobia. this research was conducted using descriptive qualitative methods, data collection techniques using indirect communication techniques with the help of questionnaires Questionnaires as a data collection tool. The population in this study is categorized by the characteristics of young people of productive marriage age, namely 21-25 years of age who have experienced the phenomenon of Gamophobia or fear of establishing a marriage relationship against the background of divorced parents. the sample in this study amounted to 3 people using Purposive Sampling technique. from this study it was found that the Gamophobia phenomenon occurred due to deep untreated trauma in the past due to parental divorce which shaped the participants' mindset and perspective on marriage relationships.